The Function of Integrative Approach in the Initial Understanding of Spatial Relations - Marija S. Vukobradović; Jasmina V. Milinković (University of Belgrade, Teacher Education Faculty, 2020)
The paper examines and analyzes the development of initial spatial reasoning. The aim of the paper is to consider to what extent the work on an integrative content contributes to the preschool children's initial understanding of spatial relationships. It explains how preschoolers build spatial relationships. Also, theoretical aspects of the integration of educational content are discussed. Based on the analysis of theoretical and empirical contributions, the importance of the development of spatial reasoning for the overall development of mathematical thinking has been determined. The empirical part presents the results of an action research. Using the descriptive-analytical method, the method of exploring non-causal relationships and relationships, and using descriptive action empirical study, the possibilities of developing spatial relationships were examined using an integrative approach. The results of the research confirm the expectation that an integrated approach creates the conditions for the development of spatial orientation skills in preschool children.